Multimedia Interaktif Genially untuk Pembelajaran Menulis Cerita Pengalaman Kelas IV Siswa Sekolah Dasar - Rohmah Riadini; Maryam Isnaini Damayanti; Heri Pranowo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
. This research is motivated by the low ability to write experiential stories of fourth-grade elementary school students, which is triggered by conventional learning methods and minimal use of media. The purpose of this study is to design interactive multimedia assisted by the Genially application on the material of writing experiential stories, which must meet the standards of validity, practicality and effectiveness. The method used is Research and Development (R&D) with the ADDIE framework (Analysis, design, development, implementation, evaluation). The research subjects consisted of 20 fourth-grade elementary school students. Data were collected through interviews, validation questionnaires, teacher and student response questionnaires, and pretests and posttests. The results of the study showed that Genilly interactive multimedia obtained a media validation percentage of 96%, material validation of 98% with a very valid category. The results of practicality obtained a percentage of 9a% from teachers and 98.3% from students with a very practical category. The effectiveness results showed an increase in learning outcomes with an N-Gain value of 0.91 in the proficient category, 0.74 in the developing category, and 0.71 in the need for guidance category, which is included in the high category. Thus, Genially interactive multimedia is suitable for use as a learning medium to help improve writing skills.